EFEITO DA SUPLEMENTAÇÃO MINERAL SOBRE O CRESCIMENTO E DESENVOLVIMENTO DE BEZERROS DA RAÇA NELORE - AMORIM, Lidianny dos Santos; PALERMO, Suyane Barros Chimene; GONÇALVES, Isabela Pinto; ARRUDA, Rosana Moreira da Silva; FERRAZ, André Luiz Julien; OLIVEIRA, Dalton Mendes (ANAIS DO ENIC, 2023)
-